Thanks to all those who reviewed for Biological Procedures Online in 2015. Issue 1 (December 2016) - Li, Shulin
Contributing reviewers A peer-reviewed journal would not survive without the generous time and insightful comments of the reviewers, whose efforts often go unrecognized. Although final decisions are always editorial, they are greatly facilitated by the deeper technical knowledge, scientific insights, understanding of social consequences, and passion that reviewers bring to our deliberations. For these reasons, the Editor-in-Chief and staff ofBiological Procedures Online warmly thank the 30 reviewers whose comments helped to shape the journal, for their invaluable assistance with review of manuscripts in Volume 17 (2015).